APPLICATION OF MODERN METHODS IN LEARNING ENGLISH IN HIGHER EDUCATIONAL INSTITUTIONS AND ITS ADVANTAGES - Gazieva Shakhnoza (Research Focus International Scientific Journal, 2025)
This thesis discusses the importance and effectiveness of using modern methods in teaching English in higher education institutions. It discusses how modern methods such as interactive teaching methods, the use of technology, hybrid learning, accelerated courses and contextual approaches are used and how students effectively implement the language learning process through them. In addition, it emphasizes the importance of modern teaching approaches in increasing students’ motivation to learn English and ensuring their scientific and academic success.